2001
DOI: 10.1007/s002030000231
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen requirement for denitrification by the fungus Fusarium oxysporum

Abstract: The effects of dioxygen (O2) on the denitrification activity of the fungus Fusarium oxysporum MT-811 in fed-batch culture in a stirred jar fermentor were examined. The results revealed that fungal denitrifying activity requires a minimal amount of O2 for induction, which is repressed by excess O2. The optimal O2 supply differed between the denitrification substrates : 690 micromol O2 x h(-1) (g dry cell wt.)(-1) for nitrate (NO3-) and about 250 micromol O2 x h(-1) (g dry cell wt.)(-1) for nitrite (NO2-). The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
95
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 21 publications
1
95
2
Order By: Relevance
“…7) F. oxysporum catalyzes the conversion of NO 3 À or NO 2 À to N 2 O under O 2 -limited conditions. 2,8) The cellfree dissimilatory NO 3 À reductase (dNar) and NO 2 À reductase (dNir) activities of F. oxysporum can be reconstituted using artificial electron donors that are also effective in reconstituting the activity of their bacterial counterparts. 2,9,10) The fungal denitrifying system is located in the respiring organelle mitochondrion, and is coupled to the mitochondrial electron transport chain to produce ATP.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…7) F. oxysporum catalyzes the conversion of NO 3 À or NO 2 À to N 2 O under O 2 -limited conditions. 2,8) The cellfree dissimilatory NO 3 À reductase (dNar) and NO 2 À reductase (dNir) activities of F. oxysporum can be reconstituted using artificial electron donors that are also effective in reconstituting the activity of their bacterial counterparts. 2,9,10) The fungal denitrifying system is located in the respiring organelle mitochondrion, and is coupled to the mitochondrial electron transport chain to produce ATP.…”
mentioning
confidence: 99%
“…14) We further found that expression of the fungal denitrifying system is regulated by the oxygen (O 2 ) supply, and that denitrification by F. oxysporum requires a minimal amount of O 2 for induction, and is repressed by excess O 2 . 8) It has been reported that an optimal O 2 supply is dependent on denitrified substrates, and that the values are 690 mmol O 2 h À1 g À1 dry cells for NO 3 À and 250 mmol O 2 h À1 g À1 dry cells for NO 2 À . 8) The final denitrified product of NO 3 À or NO 2 À by F. oxysporum is N 2 O, because this fungus does not contain an N 2 O reductase enzyme.…”
mentioning
confidence: 99%
See 3 more Smart Citations